2006
DOI: 10.1016/j.neuron.2006.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Son of Sevenless Directly Links the Robo Receptor to Rac Activation to Control Axon Repulsion at the Midline

Abstract: Son of sevenless (Sos) is a dual specificity guanine nucleotide exchange factor (GEF) that regulates both Ras and Rho family GTPases and thus is uniquely poised to integrate signals that affect both gene expression and cytoskeletal reorganization. Here, using genetics, biochemistry, and cell biology, we demonstrate that Sos is recruited to the plasma membrane, where it forms a ternary complex with the Roundabout receptor and the SH3-SH2 adaptor protein Dreadlocks (Dock) to regulate Rac-dependent cytoskeletal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 48 publications
(73 reference statements)
2
93
0
Order By: Relevance
“…Interestingly, the axon defects found in vav;trio double mutants are reminiscent of those observed in triple loss-of-function Rac mutants (Hakeda-Suzuki et al, 2002). Sos is another GEF that have been implicated in axon guidance during embryonic CNS formation through the activation of Rac (Yang and Bashaw, 2006). Removal of sos results in midline crossing defects similar to those described here for vav (Fritz and VanBerkum, 2000) and (Fig.…”
Section: Genetic Interactions Between Vav and Other Gefssupporting
confidence: 71%
See 1 more Smart Citation
“…Interestingly, the axon defects found in vav;trio double mutants are reminiscent of those observed in triple loss-of-function Rac mutants (Hakeda-Suzuki et al, 2002). Sos is another GEF that have been implicated in axon guidance during embryonic CNS formation through the activation of Rac (Yang and Bashaw, 2006). Removal of sos results in midline crossing defects similar to those described here for vav (Fritz and VanBerkum, 2000) and (Fig.…”
Section: Genetic Interactions Between Vav and Other Gefssupporting
confidence: 71%
“…For instance, beside its function in longitudinal axon growth, Trio has been involved in promoting commissure formation through its interaction with the attractive Netrin receptor Frazzled (Forsthoefel et al, 2005). Furthermore, another GEF, Sos, has been proposed to mediate Rac activation downstream of the Robo receptor to control axon repulsion at the midline (Yang and Bashaw, 2006). In this scenario, Vav, Sos, and Trio could coexist and be activated in response to different guidance molecules to control distinct aspects of axon guidance during the formation of the CNS.…”
Section: Vav and Other Gefsmentioning
confidence: 99%
“…10, C and D). Accordingly, it has been shown that in both mammalian cells and Drosophila embryos Slit activates Rac-1 by recruiting the guanine-nucleotide exchange factor (GEF) Sos to Robo (Fan et al, 2003;Yang and Bashaw, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…During axon guidance the repulsive action of Slit-2 is mediated, among other factors, by changes in the activity of Cdc-42 and Rac-1, two members of the Rho-like family of small GTPases (Wong et al, 2001;Fan et al, 2003;Yang and Bashaw, 2006). Because Rac-1 is required for production and stabilization of cell-cell contacts (Sahai and Marshall, 2002) and Cdc-42 is a well-known inducer of filopodia formation (Nobes and Hall, 1995), we speculated that the reduced strength of intercellular junctions and the increased production of filopodia observed in Slit-2-deficient cells could be due to a Figure 7.…”
Section: Effects Of the Modulation Of The Slit/robo Pathway On Hgf-dementioning
confidence: 99%
“…For each group of cells, at least 10 cells were randomly selected for quantification. Average fluorescence intensity was calculated using NIH Image J software, as previously described (Yang and Bashaw, 2006).…”
Section: Cell Immunofluorescencementioning
confidence: 99%